2018
DOI: 10.1111/apel.12233
|View full text |Cite
|
Sign up to set email alerts
|

Performance drivers in the casino industry of South Korea

Abstract: The purpose of this study is to understand the relationship between the performance drivers and financial performance of the South Korean casino industry. Data were collected from all 17 casinos in South Korea throughout 2015 and evaluated with path analysis using AMOS. Results revealed significant relationships among visitor type (domestic vs. foreign), total number of visitors, and casino revenue. Moreover, the total number of visitors affected the table games and revenues of casinos. Among implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Research from a Korean creative content agency, for example, has revealed a rise in exports from the Korean broadcasting industry. Korean pop culture is centered on Asia, and Hallyu has become a source of national competitiveness [3][4][5]. As Hallyu cultural content has gained in popularity, the popularity of Korean products related to Korean pop culture has risen as well [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research from a Korean creative content agency, for example, has revealed a rise in exports from the Korean broadcasting industry. Korean pop culture is centered on Asia, and Hallyu has become a source of national competitiveness [3][4][5]. As Hallyu cultural content has gained in popularity, the popularity of Korean products related to Korean pop culture has risen as well [6].…”
Section: Introductionmentioning
confidence: 99%